miRNA-125b-5p-rich exosomes derived from fibro-adipogenic progenitors promoting muscle regeneration through inducing pro-regenerative macrophages - Meng-meng Yang; Jing-ya Luo; Jia Cai; Jin Qian; Xiao-yan Zhu; Hui-zhen Zou; Gao-ming Li; Jing Dai; Huang Zhu; Wei Li; Li-dan Zhang; Xia Kang (Stem Cell Research & Therapy)
Abstract It is still unclear the role of exosomes derived from fibro-adipogenic progenitors (FAP) on macrophage polarization and muscle repair. In this study, the effects of exosomes collected from primary FAPs isolated from acute injured muscles at different timepoints on macrophage polarization were compared. We found exosomes derived from FAPs isolated at 10 (days post injury, DPI) can effectively induce M2 macrophage polarization both in vitro and in vivo. In addition, the pro-regenerative capacity of macrophages can be enhanced to support the activation of MuSCs and muscle repair. As we confirmed that RNAs played an important role in mediating the function of FAPD10-exos on inducing M2 macrophage polarization, using miRNA sequencing, miR-125b-5p was screened and confirmed as the key regulator to induce M2 macrophage polarization through targeting PTPN1. Furthermore, miR-125b-5p inhibited the activation of ERK pathway through inhibiting the expression of PTPN1. Overall, FAPD10-exos as well as miR-125b-5p exerted a nano-therapeutical function for muscle repair.